Prison mental health in-reach teams, serious mental illness and the Care Programme Approach in England. (August 2017) - Brooker, Charlie; Webster, Russell
Abstract: The delivery of prison mental health services in England is examined over the last 12 years. Resources for services have grown significantly during this period and improved organisational models for the delivery of services are now in place. During this period however the challenges of working in the prison environment have increased. The paper argues that a history of sexual abuse or violence are common amongst prisoners and the Care Programme Approach (CPA) provides the vehicle to assess these histories through the use of routine enquiry. Commissioners of prison mental health services now need to ensure that teams are delivering cogent trauma-based interventions where relevant and the outcomes are measured. Highlights: Resources for prison mental health in-reach teams have increased significantly since 2003. Organisational models for mental health service delivery have also improved. However, prisons have become challenging environments in which to deliver care. The numbers of prisoners on the CPA in prison is low despite NHS England policy. For those on the CPA in prison there is no evidence that routine enquiry takes place.